2008
DOI: 10.1007/s10661-007-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Applicability of Regulatory Leaching Tests for Assessing Lead Leachability in Contaminated Shooting Range Soils

Abstract: The toxicity characteristic leaching procedure (TCLP) is the current US-EPA standard protocol to evaluate metal leachability in wastes and contaminated soils. However, application of TCLP to assess lead (Pb) leachability from contaminated shooting range soils may be questionable. This study determined Pb leachability in the range soils using TCLP and another US-EPA regulatory leaching method, synthetic precipitation leaching procedure (SPLP). Possible mechanisms that are responsible for Pb leaching in each lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Similar results were observed by Cao et al (2008), who reported that the average Pb dissolution rate from the soil during the first 1 h was several times higher than at the next sampling time at pH = 3. Although Pb dissolution was slightly slower after 18 h, the Pb concentrations continued to increase with time, especially for Pb(NO 3 ) 2 -soil and PbCO 3 -soil.…”
Section: Soil Properties and Lead Leachabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were observed by Cao et al (2008), who reported that the average Pb dissolution rate from the soil during the first 1 h was several times higher than at the next sampling time at pH = 3. Although Pb dissolution was slightly slower after 18 h, the Pb concentrations continued to increase with time, especially for Pb(NO 3 ) 2 -soil and PbCO 3 -soil.…”
Section: Soil Properties and Lead Leachabilitysupporting
confidence: 90%
“…Similar results were reported by Halim et al (2004) and Ghosh et al (2004), who argued that the TCLP did not simulate the pH-Eh conditions in landfills and demonstrated that the test underestimated As leaching from bearing solids and that equilibrium was not achieved within 18 h of standard exposure time. Cao and Dermatas (2008) investigated the leachability of Pb in shooting range soils using the TCLP and showed that Pb concentrations and solution pH values were not at equilibrium after the standard extraction time of 18 h due to continued dissolution of metallic Pb particles and the re-precipitation of Pb as cerussite. Rubinos and Barral (2013) reported that the standard TCLP largely underestimated the release of trace metals from bauxite red mud because of its high capacity for neutralizing acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the SPLP test was regarded as an applicable test to evaluate metal leaching from inorganic wastes such as contaminated soils (Cao and Dermatas 2008). Our SPLP data show that the success of metal encapsulation with biochar is dependent on several contributing factors including the type of metal, heating temperature and biomass addition.…”
Section: Discussionmentioning
confidence: 74%
“…Lead concentrations as high as 60,600 mg/kg from a backstop berm have been reported (Cao et al, 2005). Military and sport ranges can be similar with respect to lead loading, but there are significant differences-the foremost being the size of the projectiles.…”
Section: Introductionmentioning
confidence: 99%